Soul Healing Ubud as a Spiritual Tourism Attraction in Bali - I Made Wira Putrayasa; I Made Sugata; I Made Wiradnyana (Institut Pariwisata dan Bisnis Internasional, 2026)
Global tourism has shifted toward transformative experiences, positioning spiritual tourism as a significant wellness segment. This study analyzes Soul Healing Ubud as a socio-cultural construct that integrates Balinese traditional healing into a wellness tourism framework. Using a qualitative case study with observations and in-depth interviews involving practitioners, tourists, and local community members, the research examines the operationalization of these practices within sustainable tourism. Findings reveal that Soul Healing Ubud transforms indigenous values into a structured spiritual product, fostering socio-cultural preservation, economic diversification, and psychological well-being. By aligning local wisdom with wellness management, this model provides a strategic alternative for sustainable development, mitigating the impacts of mass tourism while ensuring the continuity of cultural heritage. These results underscore the potential of spiritual-based wellness to strengthen destination resilience and provide transformational value for visitors.